UPAYA MENINGKATKAN HASIL BELAJAR SISWA DALAM MATA PELAJARAN BIOLOGI MELALUI MODEL PEMBELAJARAN COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) PADA SISWA KELAS X IPA 5 SMA N 1 Pasaman - Pardede, Frida (STKIP Pesisir Selatan, 2018)
Based on the results of students studying Class X IPA 5 SMA N 1 Pasaman in Biology subjects found that the results of student learning in Biology subjects is still very low. The average student learning outcomes are still under the KKM. The purpose of this study is to describe and obtain information about efforts to improve student learning outcomes in Biology sub Subjects Describe the characteristics Archaebacteria and Eubacteria and its role for life through Cooperative Integrated Reading and Composition (CIRC) Learning Model in Class X IPA 5 SMA N 1 Pasaman Pasaman Barat Regency. This research is a classroom action research. The research procedures in this research include planning, action, observation and reflection. This study consists of two cycles with four meetings. The subjects consisted of 30 students of Class X IPA 5 SMA N 1 Pasaman. The data were collected using observation sheet and daily test. Data were analyzed using percentages. Based on the results of the research and discussion that have been proposed, it can be concluded that Cooperative Integrated Reading and Composition Learning Model (CIRC) can improve student learning outcomes in Biology sub subjects Describe the characteristics Archaebacteria and Eubacteria and its role for life in SMA N 1 Pasaman. Student learning outcomes from cycle I to cycle II. Student learning outcomes in cycle I was 49.36 (Less Good) increased to 83.69 (Good) with an increase of 34.33%.